2017
DOI: 10.1158/0008-5472.can-17-0496
|View full text |Cite
|
Sign up to set email alerts
|

LSD1-Mediated Epigenetic Reprogramming Drives CENPE Expression and Prostate Cancer Progression

Abstract: Androgen receptor (AR) signaling is a key driver of prostate cancer, and androgen-deprivation therapy (ADT) is a standard treatment for patients with advanced and metastatic disease. However, patients receiving ADT eventually develop incurable castration-resistant prostate cancer (CRPC). Here, we report that the chromatin modifier LSD1, an important regulator of AR transcriptional activity, undergoes epigenetic reprogramming in CRPC. LSD1 reprogramming in this setting activated a subset of cell-cycle genes, in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 50 publications
3
63
0
Order By: Relevance
“…Microarray profiling revealed that LSD1 inhibition led to differential expression of genes, and further comprehensive analysis showed a significant downregulation of several genes associated with cell-cycle progression and therefore leading to a cell-cycle arrest. The gene expression profiles are consistent with the work of Liang and colleagues, who also showed deregulation of cell-cycle-related genes upon LSD1 inhibition (35). Interestingly, classification of the differentially expressed genes identified the G 2 -M DNA damage checkpoint regulation pathway to be significantly activated, and the mitotic roles of PLK pathway to be significantly downregulated after LSD1 inhibition.…”
Section: Discussionsupporting
confidence: 87%
“…Microarray profiling revealed that LSD1 inhibition led to differential expression of genes, and further comprehensive analysis showed a significant downregulation of several genes associated with cell-cycle progression and therefore leading to a cell-cycle arrest. The gene expression profiles are consistent with the work of Liang and colleagues, who also showed deregulation of cell-cycle-related genes upon LSD1 inhibition (35). Interestingly, classification of the differentially expressed genes identified the G 2 -M DNA damage checkpoint regulation pathway to be significantly activated, and the mitotic roles of PLK pathway to be significantly downregulated after LSD1 inhibition.…”
Section: Discussionsupporting
confidence: 87%
“…36 LSD1 was found to promote CRPC also through epigenetic programming to induce CENPE, a centromere-binding protein and mitotic kinesin, expression. 37 LSD1 is significantly upregulated in CRPC, which may suggest serve as a predictive biomarker of aggressive prostate cancer. Targeting LSD1 in conjunction with AR antagonists may also be a promising therapeutic approach to treat CRPC.…”
Section: Histone Modificationsmentioning
confidence: 97%
“…Lysine-specific demethylase 1 (LSD1) functions as a transcriptional repressor of AR-regulated enhancers through H3K4 demethylation and as an ARlinked coactivator through interaction with CoREST and histone H3 Thr6 phosphorylation (H3T6ph) (Cai et al 2011(Cai et al , 2014. LSD1 also promotes prostate cancer cell survival through activation of a gene network associated with a lethal prostate cancer independent of its demethylase function (Sehrawat et al 2018) and promotes CRPC through epigenetic programming to induce CENPE expression (Liang et al 2017).…”
Section: Epigenetic Deregulationmentioning
confidence: 99%